3D-Printed Coating of Extended-Release Matrix Tablets: Effective Tool for Prevention of Alcohol-Induced Dose Dumping Effect - Barbora Skalická; Kevin Matzick; Alena Komersová; Roman Svoboda; Martin Bartoš; Luděk Hromádko (MDPI AG, 2021)
Tablets used for extended drug release commonly contain large amounts of drugs. The corresponding drug release mechanism thus has to be well-known and invariable under numerous conditions in order to prevent any uncontrolled drug release. Particularly important is the stability and invariability of the release mechanism in the presence of alcohol due to the possible occurrence of the dose dumping effect. The effect of 3D printing (3DP) coating on the drug release mechanism and the drug release rate was studied as a possible tool for the prevention of the alcohol-induced dose dumping effect. Three types of matrix tablets (hydrophilic, lipophilic, and hydrophilic-lipophilic) were prepared by the direct compression method and coated using 3DP. The commercial filament of polyvinyl alcohol (PVA) and the filament prepared from hypromellose by hot melt extrusion (HME) were used as coating materials. Both coating materials were characterized by SEM, DSC, Raman spectroscopy, and PXRD during particular stages of the processing/coating procedure. The dissolution behavior of the uncoated and coated tablets was studied in the strongly acidic (pH 1.2) and alcoholic (40% of ethanol) dissolution media. The dissolution tests in the alcoholic medium showed that the Affinisol coating was effective in preventing the dose dumping incidence. The dissolution tests in the acidic dissolution media showed that the Affinisol coating can also be useful for the delayed release of active substances.